Rodent composition, population and damages of subsistence farms in selected local (2020)
Rodents are main causes of huge crop losses in most field and stored produce of all vertebrate pests of agricultural importance in developing countries. Information on the damages caused by rodents in Oyo State, Nigeria is largely obsolete and poorly documented. The study was carried out in five purposively selected agrarian local government areas (LGAs) - Ibarapa North, Ibarapa Central, Ibarapa East, Lagelu, and Iddo local governments - in Oyo state, Nigeria. Fifty Structured questionnaires were used to randomly assess knowledge of farmers in Oyo State Agricultural Development Programme on rodents and their importance in each LGA. Kill traps were used to estimate population density of rodents in the study area over a 14-week period. All data were descriptively analysed. Cricetomys gambianus, Mus musculus, Sciurus carolinensis, Xerus erythropus, Oryctolagus cuniculus, and Rattus rattus were identified as pests of crops in the study area. High rodent damage ratings were recorded in maize in all LGAs, with infestation rating in Ibarapa East being (2.5), Ibarapa Central LGA (2.0), Iddo (2.5), Lagelu (3.0), Ibarapa North (2.5). Lowest damages were reported in pineapple (Range: 0.0 -.0.5). In storage, maize, cocoyam, cassava, oil palm kernels, yam and pineapple were mostly affected. Rodent density estimates ranged from 22 to 174/ha at Lagelu, 30 to 923/ha at Ibarapa Central, and 85 to 167/ha at Iddo. The inter-connectivity resulting from incomplete land fragmentation made management and control of rodents difficult. Farmers are encouraged to synchronize their management and control strategies in time and space, while the government includes rodent management in agricultural programme packages.